Determinants of Profitability of Islamic Commercial Banks in Indonesia with Third-Party Funds as A Moderating Variable - Iqbal Rafiqi; Annisa Annisa (Al-Amien Prenduan for Islamic Institute, 2023)
Profitability is one of the ratios needed to assess the health of a bank. The health of a bank is a reflection of the current and future condition of the bank. So many factors that affect the level of profitability of a bank are reviewed from several existing studies. The purpose of this study is to find out whether the independent variables chosen by the researcher affect the profitability of the bank and whether third-party funds can moderate the relationship between the two. Sharia Commercial Banks (BUS) as many as 13 BUS became the population, while the research sample was 5 BUS choosen based on judgement / purposive sampling techniques. The data analysis technique used is moderated regression analysis with the SPSS20 application. Profitability is a dependent variable while the independent variables are capital adequacy ratio (CAR) and financing deposit to ratio (FDR), and third-party funds (DPK) as moderating variables. The results of the study based on the t-test of CAR, FDR and DPK did not have a significant effect on the profitability of Islamic Commercial Banks in Indonesia. And based on the results of the moderation regression analysis test, DPK can moderate the relationship between CAR and FDR variables to the profitability of Islamic Commercial Banks.